Optimization of chitosan and sodium carboxymethylcellulose as mucoadhesive system in theophylline tablet - Irawan, Eka Deddy; ., Farhana (Indonesian Journal of Pharmacy, 2011)
Mucoadhesive  tablet  for  asthma  treatment  were  prepared  by  mixing theophylline  with  two  variations  of  polymers.  The  purpose  of  this  research  was to  controlled  drug  release  from  the  dosage  form.  Theophylline  mucoadhesive tablets  were  prepared  by  direct  compression  using  chitosan  and  sodium carboxymethylcellulose  as  mucoadhesive  polymers.  Mucoadhesive  strength measured  using  rabbit  gastric  mucosa  and  in  vitro  drug  dissolution  was subjected  in  a  hydroclorid  acid  buffer  pH  1.2  for  10  hours.  The  optimized formula  was  obtained  by  analyzing   both  evaluation  using  factorial  design. Formula  with  5.4  %  of  chitosan  and  14.5  %  of  sodium carboxymethylcellulose followed zero order kinetics. The optimized formulation showed by 8.38-10.91% of  chitosan  and  28.84-29.09%  of   sodium  carboxymethylcellulose  with mucoadhesive strength between 25-40 gram and 43.5%-55% drug was released in 10 hours.Key words: Mucoadhesive, chitosan, CMC Na, E, factorial design.